# Numerical Expressions Involving Whole Numbers

This topic will discuss about numerical expressions involving whole numbers. In numerical expressions there will be various operations that are to be performed like addition, subtraction, multiplication and division. We know that whole numbers are positive integers including zero. Therefore, we would follow the BODMAS rule in solving the numerical expressions involving whole numbers.

We have learnt in previous subtopics the meaning of the extended meaning of BODMAS.

B = Brackets

O = Of

D = Divison

M = Multiplication

S = Subtraction

Here are few examples to illustrate numerical expressions involving whole numbers following BODMAS rule:

1. 20 + 10 × 60 ÷ 6 + 3

Solution:

20 + 10 × 60 ÷ 6 + 3

= 20 + 10 × 10 + 3

= 20 + 100 + 3

=123

Explanation:

We will first do division (i.e. 60/6 = 10), then multiplication (i.e. 10 multiplied by 10 = 100), then followed by addition. Then we will add 20, 100 and 3 to get the final answer as 123.

2. 56 ÷ 8 + 23 – 8 × 0

Solution:

56 ÷ 8 + 23 – 8 × 0

= 7 + 23 – 8 × 0

= 7 + 23 – 0

= 30 – 0

= 30

Explanation:

We will first divide 56 by 8 to get 7 then we will do multiplication that is 8 multiplied by 0 is 0 leaving the addition and subtraction part as it is. Now we have 7 + 23 – 0, so we will first add 7 and 23 to get 30 and then subtract 0 from it to get 30 as final answer.

3. 3 × 4 ÷ 2 + 6 – 7 × 1

Solution:

3 × 4 ÷ 2 + 6 – 7 × 1

= 3 × 2 + 6 – 7 × 1

= 6 + 6 – 7

= 12 – 7

= 5

Explanation:

First carry out division (i.e. 4 divided by 2), then there are two operation on multiplication. We will complete those two multiplication first after the division leaving other addition and subtraction as it is. After completing the two multiplication we have 6 + 6 – 7. We will first add both the 6’s to get 12 then subtract 7 from it. The final result is 5.

4. 78 +26 – 23 × 0 + 49 of 7 ÷ 49

Solution:

78 + 26 – 23 × 0 + 49 of 7 ÷ 49

= 78 + 26 – 23 × 0 + 343 ÷ 49

= 78 + 26 – 23 × 0 + 7

= 78 + 26 – 0 +7

= 78 + 26 +7 – 0

= 111 – 0

= 111

Explanation:

First do the ‘Of’ function which is actually nothing but multiplication (i.e. 49 of 7 to get 343). Then 343 is divided by 49 to get7. Next is multiplication (i.e. 23 multiplied by 0). Then followed by addition (i.e. 78 + 26 + 7 to get 111) and finally subtraction (i.e. 0 subtracted from 111 is 111).

## You might like these

• ### Highest Common Factor of Three Numbers by using Division Method

This topic would discuss about finding highest common factor using the division method. We have already learnt finding the highest common factor by prime factorization method but it is not suitable when we are dealing with large numbers. Division method is quite convenient

• ### Find Highest Common Factor of Two Numbers by using Division Method

We have already learnt the method of finding highest common factor using division method. Here are few more examples given to clear your understanding, concepts and improve your knowledge on how to find H.C.F. this topic would provide a wide range of examples will help the